Voice characteristics of some sheep: Utilization to estimation of genetic distance - Eko Handiwirawan; Ronny Rachman Noor; Cece Sumantri; . Subandriyo (Jurnal Ilmu Ternak dan Veteriner, 2015)
Sound analysis has been carried out in various activities including identification and differentiation of species as well as the preparation of the taxonomy of some animals’ species because of several advantages, including no need to capture or too close to the subject observed. Analysis of voice used to differentiate and to estimate of breeds’ sheep genetic distance has not been reported. This research was conducted to study the character of a few breeds’ sheep sound and likely to be used as a predictor of genetic distance between breeds of sheep. The study was conducted in the Animal House at Indonesian Research Institute for Animal Production, Bogor.  A total of 20 head adult of five sheeps (St. Croix cross / SC, Barbados Black Belly cross / BC, Local Garut/LG, Composite Garut / KG and Composites Sumatra / KS) used in this study. Call sound recorded using a digital voice recorder. Sound analysis performed by Raven Software Pro 1.3 for Windows to count as many as 24 variables sound. Analysis of variance of each variable sound was performed using PROC GLM of SAS software Ver. 9.0. It used PROC CANDISC for canonical discriminant analysis and then PROC TREE to build a dendogram. The results showed that there were variations in amplitude, energy, power and frequency variables among the five breeds of sheep. By plotting canonical, LG, KS and BC sheep were from a different group. It was concluded that the sound characteristics variables which can be used as a differentiator breeds of sheep were the third quartile frequency, center frequency, maximum frequency and the first quartile time. Dendogram showed that KG sheep was in the less accurate group. Genetic distance estimation method using voice characteristic data may be applied on sheep. Key Words: Characteristics, Call Voice, Differentiation, Genetic Distance, Sheep